Behavioral adaptation in diet maintains nutrient composition in an isolated, confined, and extreme environment in Antarctica - Klos, Bea; Reinhardt, Daniela; Meyer, Andrea; Albertsen, Nadja; Thoolen, Stijn; Hagson, Hannes; Possnig, Carmen; Enck, Paul; Mack, Isabelle (Frontiers in Nutrition, 2025)
BackgroundComprehensive monitoring of dietary intake in isolated, confined, and extreme (ICE) environments is critical to elucidate physiological adaptations and to mitigate nutrition-related health risks. Although a reduction in energy intake has consistently been reported under ICE conditions, the underlying nutritional determinants remain insufficiently characterized. This study aimed to systematically examine longitudinal changes in dietary intake during a 1-year overwintering mission at Concordia Station, Antarctica.MethodsDietary intake data were collected from 34 crewmembers across three overwintering campaigns at Concordia Station, each lasting 12 months with ad libitum food access. Assessments were conducted at five time points (T0: baseline; T1–T3: in-mission; T4: follow-up) using a validated Food Frequency Questionnaire covering 130 items. Nutrient intake was calculated for energy, macro- and micronutrients. Gastrointestinal symptoms were evaluated using a standardized questionnaire.ResultsParticipants experienced a gradual body weight loss during overwintering (−4.5% ± 6.1%), indicating a sustained energy deficit. Nevertheless, the overall macronutrient distribution remained stable over time, as opposing shifts in the intake of specific food groups balanced each other out. Although fiber intake temporarily declined (p < 0.001), gastrointestinal symptoms remained largely absent, suggesting that the dietary shifts did not result in notable functional impairments.ConclusionDespite environmental constraints and limited availability of fresh foods, participants maintained a rather stable nutrient distribution, suggesting broadly adequate diet quality. The observed weight loss therefore reflects insufficient intake rather than poor diet quality. These findings highlight the adaptability of dietary behavior under ICE conditions and underscore the importance of flexible yet well-structured provisioning strategies to ensure nutritional sufficiency and physiological resilience during long-duration stays in isolated and extreme environments.